Remote sensing reveals Antarctic green snow algae as important terrestrial carbon sink - Gray, Andrew; Krolikowski, Monika; Fretwell, Peter; Convey, Peter; Peck, Lloyd S.; Mendelova, Monika; Smith, Alison G.; Davey, Matthew P. (Nature Publishing Group UK, 2021)
Abstract: We present the first estimate of green snow algae community biomass and distribution along the Antarctic Peninsula. Sentinel 2 imagery supported by two field campaigns revealed 1679 snow algae blooms, seasonally covering 1.95 × 106 m2 and equating to 1.3 × 103 tonnes total dry biomass. Ecosystem range is limited to areas with average positive summer temperatures, and distribution strongly influenced by marine nutrient inputs, with 60% of blooms less than 5 km from a penguin colony. A warming Antarctica may lose a majority of the 62% of blooms occupying small, low-lying islands with no high ground for range expansion. However, bloom area and elevation were observed to increase at lower latitudes, suggesting that parallel expansion of bloom area on larger landmasses, close to bird or seal colonies, is likely. This increase is predicted to outweigh biomass lost from small islands, resulting in a net increase in snow algae extent and biomass as the Peninsula warms.